Doxorubicin alters the disposition of phenytoin by reducing its metabolic elimination and binding affinity to serum albumin in rats. (18th December 2021) - Fukuno, Shuhei; Nagai, Katsuhito; Yamaoka, Shizuka; Yamada, Fuka; Mizumoto, Haruna; Ito, Takuya; Konishi, Hiroki
Abstract: Objectives: We investigated the pharmacokinetic interaction of doxorubicin (DOX) with phenytoin (PHT) and the underlying mechanism in rats to clarify why the serum PHT concentration decreases despite the impaired PHT metabolic capacity in patients receiving DOX. Methods: Rats were administered 15 mg/kg of DOX or saline alone. The pharmacokinetic disposition of intravenously administered PHT was examined 4 days after DOX exposure. Enzyme kinetics of CYP2C-dependent PHT p -hydroxylation were analysed using hepatic microsomes. The unbound PHT concentration in serum was measured by the ultrafiltration method, and the relationship between the unbound fraction ( f u ) and serum albumin level was assessed. Key findings: The total clearance (CLtot ) of PHT was significantly increased by DOX, but the activity of PHT p -hydroxylation conversely decreased. The unbound serum PHT concentration and its f u were significantly higher in the DOX group than in the control group, and the CLtot / f u, a measure of intrinsic clearance, significantly decreased. An increase in the f u was observed even when using a serum sample with an albumin concentration equal to that in the control group. Conclusions: DOX treatment increases the unbound serum PHT concentration by depressing the metabolic capacity and alters the total PHT by reducing serum albumin and its affinity to PHT.